Bio Effect of Seven Aqueous Plant Extracts Against Khapra Beetle Trogoderma Granarium Everts (NTU Journal of Agriculture and Veterinary Science, 2022)
The study showed the effectiveness of the aqueous extracts of seven plant species for Clove buds (Syzygium aromaticum), Garlic seed (Allium sativum), Thyme leaves (Thymus vulgaris), Eucalyptus leaves (Eucalyptus oleosa), Sage (Salvia officinalis), Alaaya leaves (Eminium spiculatum), and red hot pepper fruits (Capsicum annuum) with five different concentrations (1.5, 3, 5, 7.5 and 10) % in some Biological aspects of the Khapra beetle larvae Trogoderma granarium Everts. The aqueous extract of sagebrush showed the highest lethal effect, as the killing rate was 100% at a concentration of 5%, and toxicity index and toxicity efficiency amounted to 100, 28, and 23, respectively, compared to the rest of the studied plants. It was noted that the aqueous extracts of plants sagebrush and sagebrush tested showed the characteristic of repelling insects and that the sagebrush plant gave the highest repelling rate of 63.33%, while the plants of garlic, hot pepper, cloves, thyme, and eucalyptus showed the characteristic of attraction and that the aqueous extract of cloves gave the highest attraction rate of 73.33.